Digital technologies for climate action, disaster resilience, and environmental sustainability. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
It provides an overview of the available technology types and their applications and assesses opportunities and barriers for their uptake. The publication provides insights on how digital technologies can be operationalized in the Asian Development Banks developing member countries, including to support nationally determined contributions and green recovery efforts.
The Landscape of Digital Technologies - - The Role of Digital Technologies - - Selecting Digital Technologies to Address Development Objectives - - Operationalizing Digital Technologies in Developing Asia - - Conclusion - - Appendix: ADB Initiatives on Incorporating Digital Technology into Its Projects and Programs
Keywords: Information technology -- Economic aspects; Knowledge economy; Electronic book